How to boost and reach the full potential of Mugler´s perfumes brand loyalty: what should be the ideal brand architecture for Mugler - Baptista, Madalena Luz Gomes e Cruz (2022)
The main purpose of this work project is to analyze Mugler’s capacity to boost and reach the full potential of its perfumes brand loyalty to retain consumers in Portugal. Beyond desk research, 30 in-depth interviews with Mugler consumers, social media listening, and mystery client were conducted and the loyalty drivers and the relationship with the brand were evaluated. Since it is missing a low level of affection and knowledge between consumers and the brand, several recommendations were suggested. The proposed revision in the portfolio and in its communication will link Mugler with its heritage and to leverage the brand’s perception.